Reação de crisântemos a Meloidogyne incognita, Meloidogyne javanica e Meloidogyne enterolobii - Gonçalves, Lucivane Aparecida [UNESP] (2014)
This study aimed to evaluate the resistance of 14 chrysanthemum varieties to the nematodes Meloidogyne incognita, M. javanica and M. enterolobii. The experiment was conducted in a completely randomized design, consisting of 15 treatments and 4 replicates per nematode species. Each plot was constituted of one plant per pot; plants were kept in a greenhouse and inoculated with 5,000 eggs and possible juveniles of M. incognita, M. javanica and M. enterolobii. After 60 days, the rates of egg masses, the number of nematodes per gram of root and the reproduction factor were evaluated. The varieties showed immunity to M. incognita, M. javanica and M. enterolobii, except 'Capello Vermelho' and 'White Reagon', which were susceptible and resistant, respectively, to M. incognita.